Disparities in Dream Capital Among Adolescents: Focused on the Role of Arts Education in Schools of South Korea - Kim, Dooiee; Ahn, Jiyoun (Studies in Art Education, 2023)
This research explores the role of arts education in schools in relation to the regional disparities in adolescent dream capital. A total of 142 adolescents, who received either intensive arts education or general education, were surveyed in South Korea. Based on previous studies, the authors focused on four dimensions of dream capital capacity—imagination, hope, optimism, and resilience—as well as its subindicators, self-confidence and authenticity. Research findings indicate that most subdimensions of dream capital for adolescents in small and mid-sized cities were markedly lower than those in large cities. However, dream feature disparities, such as optimism and authenticity, were not found among those who received intensive arts education. This study extends the current discussion on the inequality of dream capital caused by regional disparity and offers new insights into the role of arts education in schools in alleviating these gaps.